Implementation of augmented reality herbarium malangensis website tour to enhance conservation literacy - Murni Sapta Sari; Deny Setiawan; Umi Fitriyati; Zahra Firdaus; Dinar Arsy Anggarani; Claresia Tsany Kusmayadi; Maisuna Kundariati (JINoP (Jurnal Inovasi Pembelajaran), 2024)
The biodiversity of Indonesia showed by the numerous of plant species, including one of the 89,326 species of spore plants. Along with the high diversity of various threat factors that will affect the status of a plant, knowledge about plants can be enhanced through conservation literacy using modern technology-based learning media, such as 3D modeling and augmented reality (AR) websites. AR acts as an interactive window that opens the view of conservation reality. The aim of this research is to produce a rare plant learning media product in the Bromo Tengger Semeru National Park that exists on the Malangensis Herbarium with the integration of 3D modeling websites. The method used is R&D, referring to the ADDIE model. The practicality test results obtained 91.54%, while the media effectiveness test showed with n-gain scores obtaining a result of 0.66 that media can improve conservation literacy skills in biology students of the State University of Malang. This research could provide a benchmark and literature for advanced media development on plant divisions other than Pteridophyte.